Analysis of Factors Affecting Healing of Acute Pharyngitis Viral Patients in Puskesmas I, Klungkung-Bali - Ida Ayu Manik Partha Sutema; Made Sudiari; I Gede Palguna Reganata (Warmadewa University, 2022)
Abstract Antibiotic resistance is closely related to the inappropriate use of antibiotics, namely the indication, dose, frequency, and duration of use. Permenkes No. 5 of 2014 states that acute pharyngitis is given antibiotic therapy if it meets the diagnostic criteria using the center criteria, but this criterion is difficult to apply because doctors take longer to diagnose. Previous research at the Klungkung I Primary Health Center used diagnosis utilizing a swab test. It was found that 100% of bacterial pharyngitis patients were negative. The strategy of delaying antibiotics for 3 days can prevent antibiotic resistance, but in therapy, without antibiotics, it is important to increase the effectiveness of therapy, it is deemed necessary by the researchers to conduct a study to analyze the factors that affect the recovery of patients with acute pharyngitis, which are mainly caused by viruses. Analyzing the factors that affect the recovery of viral pharyngitis patients. The design of the cross-sectional study was through observation of the medical record data of patients who came to the Klungkung Primary Health Center I for 3 months and got diagnostic facilities using the swab test. Patients who got a negative swab test were analyzed for the factors that influenced their recovery. Anti-inflammatory variables, rest, and paracetamol significantly affected the recovery of acute pharyngitis patients (p <0.05), and the importance index in CART analysis found that paracetamol was the most influential, followed by rest, administration of vitamins, and anti-inflammatory. Antibiotics, anti-allergies, and cough medicines do not affect the recovery of patients with acute pharyngitis viral. Paracetamol has the most effect on patient recovery, followed by rest and administration of vitamins, anti-inflammatory has very little effect on the recovery in patients of acute pharyngitis viral. Keywords: acute pharyngitis, cure, CART.